Pregnancy intention and phthalate metabolites among pregnant women in The Infant Development and Environment Study cohort. Issue 6 (6th April 2020) - Lyden, Grace R.; Barrett, Emily S.; Sathyanarayana, Sheela; Bush, Nicole R.; Swan, Shanna H.; Nguyen, Ruby H. N.
Abstract: Background: Preconception life style and health play a pivotal role in positively impacting the health of a pregnancy, and this includes the reduction of exposure to endocrine‐disrupting chemicals such as phthalates. We have previously demonstrated that women planning a pregnancy with assisted reproductive technology (ART) have lower phthalate metabolite concentrations than their non–ART‐using counterparts. Objective: To determine whether women who intended to become pregnant had lower phthalate metabolite concentrations than those who had an unintended pregnancy, or whether change in phthalate exposure across pregnancy differed between these two groups. Methods: A total of 721 women enrolled in The Infant Development and Environment Study (TIDES), a multicentre US prospective pregnancy cohort; 513 (71%) indicated their pregnancy was planned. Urine samples from first‐ and third‐trimester visits were analysed for 10 specific‐gravity‐adjusted, natural‐log‐transformed phthalate metabolites. Simple and multivariable linear regression, adjusting for centre, race, age, income, marital status, and parity, were employed to determine whether phthalate metabolite concentrations differed by pregnancy intention. Results: In bivariate analyses, the geometric mean concentrations of all first‐trimester and most third‐trimester phthalates were higher in women with unplanned pregnancies. However, after covariate adjustment, only first‐trimester monoisobutyl phthalate (MiBP) remained associated with pregnancy intention, and the association changed direction such that unplanned pregnancies had lower MiBP concentrations (ß −0.18, 95% CI −0.35, −0.02). Conclusions: We did not find evidence of a difference in phthalate exposure between pregnancy planners and non‐planners.